PENGEMBANGAN TES TERTULIS TWO-TIER MULTIPLE CHOICE PADA MATERI POKOK ORGANISASI KEHIDUPAN - SRI RAHAYU, ARTI (2014)
Research entitled "Development Two-tier Multiple Choice Written Test on Organization of Life" aimed to develop written test set which adapted from characteristic of Two-tier Multiple Choice Written Test which developed by Tan (2005), but the Content Standard and the matter still refer to KTSP curriculum. Written test set consists of 40 items. Descriptive's method used to describe the result of development two-tier multiple choice written test after testing twice. Then, to describe the categories of student's understanding about the matter Organization of Life building on student's pattern of answered the two-tier multiple choice written test. The result of research shows that two-tier multiple choice written test up to standard of validity, reliability, difficulty level, discriminating level, and distractor efectivity. Besides, according to student's responses, they said that two-tier multiple choice written test is difficult but more challenging and has more variation than usual Biology's items evaluation. The result of this research hopefully can give new perspective in Biology's evaluation and can guide teachers to use and to develop the same evaluation by themselves.